2013
DOI: 10.1016/j.pbb.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned reinforcement and locomotor activating effects of caffeine and ethanol combinations in mice

Abstract: A growing trend among ethanol drinkers, especially young adults, is to combine caffeinated energy drinks with ethanol during a drinking episode. The primary active ingredient of these mixers is caffeine, which may significantly interact with ethanol. We tested the two hypotheses that caffeine would enhance ethanol-conditioned place preference and also enhance ethanol-stimulated locomotor activity. The interactive pharmacology of ethanol and caffeine was examined in C57BL/6J (B6) mice in a conditioned place pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 59 publications
6
29
1
Order By: Relevance
“…In the present study, systemic administration of 1.5 g/kg of ethanol during five conditioning sessions, using an unbiased paradigm, induced robust CPP. Our result is similar to previously reported studies that indicated that a moderate dose of ethanol (1.5–2 g/kg) produced a significant CPP in C57BL/6 mice 4346. Our previous research revealed that the systemic administration of B428 impaired cocaine-induced CPP,21 suggesting that uPA inhibition can impair the capacity of environmental cues that are associated with psychostimulation to elicit approach behavior.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, systemic administration of 1.5 g/kg of ethanol during five conditioning sessions, using an unbiased paradigm, induced robust CPP. Our result is similar to previously reported studies that indicated that a moderate dose of ethanol (1.5–2 g/kg) produced a significant CPP in C57BL/6 mice 4346. Our previous research revealed that the systemic administration of B428 impaired cocaine-induced CPP,21 suggesting that uPA inhibition can impair the capacity of environmental cues that are associated with psychostimulation to elicit approach behavior.…”
Section: Discussionsupporting
confidence: 92%
“…The choice of the ethanol dose for the repeated exposure procedure was influenced by earlier work showing that the oral gavage route of administration can achieve high blood ethanol levels (Griffin et al , 2009), but also that it would not completely impair locomotion. We chose to use 15 mg/kg caffeine based on previous work showing that administration of this dose would significantly increase locomotor activity (Hilbert et al , 2013; Kaplan et al , 1989). For the exposure procedure, drugs were administered by oral gavage twice per day (at 0730h and 1530h).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that caffeine can increase ethanol drinking in rats (Kunin et al , 2000; Rezvani et al , 2013) and can promote significant ethanol-induced taste aversions (Kunin et al , 2001). Additionally, it has been reported that combinations of caffeine and ethanol, compared to either drug alone, increase locomotor activity after acute injection (Hilbert et al , 2013) or while consuming the drug mixtures in a drinking paradigm (Fritz et al , 2014). Some research has also incorporated energy drinks into animal models and shown that they can antagonize locomotor deficits with higher doses of ethanol (Ferreira et al , 2004) similar to administering only caffeine (Hilbert et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations